An Association Between Core Mutations in Hepatitis B Virus Genotype F1b and Hepatocellular Carcinoma in Alaskan Native People. Issue 1 (10th December 2018) - Hayashi, Sanae; Khan, Anis; Simons, Brenna C.; Homan, Chriss; Matsui, Takeshi; Ogawa, Kenji; Kawashima, Keigo; Murakami, Shuko; Takahashi, Satoru; Isogawa, Masanori; Ikeo, Kazuho; Mizokami, Masashi; et al.
Abstract : Hepatitis B virus (HBV) genotype F1b infection is strongly associated with hepatocellular carcinoma (HCC) in young Alaskan Native (AN) people. However, the mechanisms by which genotype F1b causes HCC are unclear. Here, we analyzed the clinical and virological significance of genotype F1b in long‐term serial samples from 20 HCC patients with HBV infection. Complete sequence analyses revealed that all isolates were genotype F1b. In the HCC patients, T1938C and A2051C mutations in the core region had accumulated significantly with A1762T/G1764A mutations in the basal core promoter (BCP) region and G1896A mutation in the precore (PC) region. Several HBV clones containing the core mutations were examined for their replication efficiency and core stability in vitro . Clones containing the A2051C mutation replicated more efficiently than the wild type in association with enhanced stability of core protein dimerization. In chimeric mice with human hepatocytes carrying BCP/PC/2051 mutant but not with wild‐type virus, liver fibrosis was induced in association with high levels of serum HBV DNA and hepatitis B surface antigen. Interestingly, microarray analysis and validation study showed that five genes associated with cell proliferation or carcinogenesis, v‐myc avian myelocytomatosis viral oncogene homolog, Grb2‐associated binding protein 2, bradykinin receptor B2, follistatin, and mitogen‐activated protein kinase kinase kinase 8, were significantly up‐regulated in human hepatocytes infected with genotype F1b, particularly the BCP/PC/2051 mutant, compared with other genotypes. Conclusion : We have identified an association between Alaska‐specific core mutations and HCC development in AN people infected with genotype F1b; accumulation of these core mutations during the course of chronic infection with genotype F1b would contribute to HCC development in AN people earlier in life.